2015
DOI: 10.1039/c4gc01529k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous conversion of all cell wall components by an oleaginous fungus without chemi-physical pretreatment

Abstract: C. echinulata FR3, a non-basidiomycete oleaginous fungus with strong lignin degradation machinery, could convert all cell wall components to lipid without chemi-physical pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Besides MnP, versatile peroxidases were described as a new family of ligninolytic peroxidases, which had a hybrid molecular architecture that combined different oxidation sites with the heme cofactor for the oxidation of some high redox potential aromatic substrates [25]. Previous reports suggested that peroxidase synergized the redox condition and the Fenton reaction to maximize aromatic polymer degradation [5,8,9]. This study indicated a similar mechanism with specific refined enzymes.…”
Section: Overview Of Differential Gene Expressionmentioning
confidence: 56%
“…Besides MnP, versatile peroxidases were described as a new family of ligninolytic peroxidases, which had a hybrid molecular architecture that combined different oxidation sites with the heme cofactor for the oxidation of some high redox potential aromatic substrates [25]. Previous reports suggested that peroxidase synergized the redox condition and the Fenton reaction to maximize aromatic polymer degradation [5,8,9]. This study indicated a similar mechanism with specific refined enzymes.…”
Section: Overview Of Differential Gene Expressionmentioning
confidence: 56%
“…The total lipids of S. cerevisiae were extracted in the form of fatty acid methyl ester (FAME) using the sulfuric acid-methanol method as previously described [34], details can be found in Supplementary method. The lipid composition was analyzed by GC-MS using a SHIMADZU-QP2010 SE GC-MS (SHIMADZU CORPORATION, Japan) equipped with a ZB-5MSi column (thickness 0.25 µm; length 30 m; diameter 0.25 mm) as previously described [34].…”
Section: Lipid Quantificationmentioning
confidence: 99%
“…sorghum and maize), brown midrib ( bmr ) mutants have been useful for reducing lignin content (Cherney et al ., ) and altering secondary cell wall composition (Palmer et al ., ), which has led to enhanced saccharification and fermentation efficiencies and improvements in ethanol yields from lignocellulosic biomass (Dien et al ., ) and in vitro digestibility (Aydin et al ., ; Oliver et al ., ). Sorghum bmr mutants have also been shown to increase yields in emerging biofuel fermentation systems that utilize lignin as a substrate for lipid synthesis (Xie et al ., ). Together this research illustrates the plasticity of plants to tolerate changes in lignin composition and the utility of modifying biomass composition for industrial purposes.…”
Section: Introductionmentioning
confidence: 97%